A computational framework for rheologically complex thermo-visco-elastic materials. (1st February 2022) - Lenarda, P.; Paggi, M.
Abstract: Fractional calculus has been proved to be very effective in representing the visco-elastic relaxation response of materials with memory such as polymers. Moreover, in modeling the temperature dependency of the material functions in thermo-visco-elasticity, the standard time–temperature superposition principle is known to be ineffective in most of the cases (thermo-rheological complexity). In this work, a novel finite element formulation and numerical implementation is proposed for the simulation of transient thermal analysis in thermo-rheologically complex materials. The parameters of the visco-elastic fractional constitutive law are assumed to be temperature dependent functions and an internal history variable is introduced to track the changes in temperature which are responsible for the phase transition of the material. The numerical approximation of the fractional derivative is employed via the so called Grünwald–Letnikov approximation. The proposed model is used to numerically solve some test cases related to relaxation and creep tests conducted on a real polymer (Ethylene Vinyl Acetate), which is used as the major encapsulant of solar cells in photovoltaics.